Danger in traffic: patients with obstructive sleep apnea syndrome - Erdogdu, Suleyman (International Journal of Research in Medical Sciences, 2020)
Background: Author aimed to investigate the presence of a driver’s license of patients with sleep apnea and obstructive sleep apnea syndrome (OSAS) and to prevent them from going into traffic until they are treated. Methods: In this study 645 hospitalized patients in the sleep lab for one night in 2017-2018 for polysomnography (PSG) test were questioned. We compared Apne Hipopne Indexes (AHI) and Body Mass Indexes (BMI). Patients who have risk for traffic accidents were identified. Results: Total 424 (66%) of 645 patients were above AHI> 15, moderate and severe Obstructive Sleep Apnea Syndrome (OSAS) was diagnosed. 221 patients (34.3%) obtained a driver’s license because they have mild OSAS (The AHI <15). 162 patients with AHI 15-30 (25.1%) had severe OSAS with medium OSAS and 262 patients (40.6%) had AHI> 30. Also, 410 patients with a driver’s license in 645 patients had BMI> 25 kg/m2 in 373 (91%). 340 (83%) of 645 patients with a driver’s license were male; 70 (17%) of them are women. All of those with a heavy vehicle license are men and the number is 110. Conclusions: To prevent possible traffic accidents, driver patients with OSAS detected by a polysomnography test should be withdrawn from the driver’s license until they receive treatment and receive an updated health report.